THE COMPOSITION AND DISTRIBUTION OF BENTHIC FORAMINIFERA AT CORAL REEF ECOSYSTEM IN THOUSANDS ISLAND - Lumban Nauli Lumban Toruan; Dedi Soedharma; Kresna Tri Dewi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
Composition and distribution of foraminifers are affected by human activities and have close association with coral reef ecosystem. The aims of this research were to investigate the benthic foraminifers’ composition and distribution in sediment of coral reef ecosystem. Eleven stations of Karang Bongkok, Pramuka, and Onrust Island were observed in this study. The sediments were taken from surface substrate up to 2 cm under the substrate. Samples were washed on sieve with mesh size 0,063 mm, and then dried in oven with 50°C of temperature for two hours. After separating from the sediment, the foraminifers were laid on foraminiferal slide and indentified using binocular microscope. The highest composition of symbiont-bearing foraminiferal assemblages which associated with reef ecosystem was in East Pramuka (78.17%) and the lowest was in South Onrust (21,83%). The opportunistic type had the highest composition in South Onrust (38.67%) and the lowest was in South Karang Bongkok. In west Pramuka had the highest composition of heterotrophic type (57.17%) and the lowest was in North Onrust (11.33%). Onrust Island was dominated by opportunistic type, indicating high nutrient. The highest amount of foraminifers’ taxa was found in Karang Bongkok with good coral reef coverage, while the lowest in Onrust facing with Jakarta Bay. Keywords: composition, distribution, benthic foraminifers, coral reef.